The distribution and length size of corbicula fluminea (ETAK) in Sungai Pergau at Gunung Reng - Eh Rak, Aweng; Ab Khalid, Nur Fasihah; Syed Omar, Sharifah Aisyah (Science Publishing Corporation Inc., 2018)
Corbicula fluminea (Bivalvia: Corbiculidae), locally known as “etak” which is the favorite freshwater clams in the Kelantan state. This study was conducted to study on Etak distribution in Sungai Pergau at Gunung Reng which is known as a recreational spot. As it is the favorite freshwater clam in the state, the data could be helpful in monitoring its presence and if in decline, remedial and replenishment could be introduced. The numbers, weight and the length measurement of C. fluminea were identified as C. fluminea parameters. In addition, water quality used (conductivity, pH, turbidity, salinity, temperature, DO and nitrate) and types of substrate were also studied to identify the habitat characteristics that affect the distribution of this species. As there was no documentation of distribution and density of C. fluminea in Sg. Kelantan, it would be difficult to compare the density and distribution of “etak” in the others river in Kelantan. In total 166 individuals of C. fluminea (77g) found at middle streams with 11-12.5mm in length. As the finding shows that, the distribution of C. fluminea at Gunung Reng was not affected by water quality. In this study shows that the most substrate ranged from 0.25mm and 0.71mm which represent sand (sand-coarse and sand-fine). It is believed that the smaller substrates help to trap more suspended materials as food for C. fluminea and the harvesting activities reduce the time for the clams to grow mature with a larger size in length.